Influence of the waste oil concentration in water on the efficiency of the aeration process in refinery wastewater treatment - Pavlović, Milan (Strojniški vestnik, 2008)
Process, aeration system and aeration method for biological treatment of wastewater with activated sludge in bio-aeration tanks are chosen based on theflow parameters, composition of the wastewater and required characteristicsof the purified water. Choosing an aeration system is a very complex question, as the capacity of oxygen introduced into the wastewater should correspond to the oxygen consumption in order to achieve the most efficient purification. This paper presents the results of experimental aeration analysis of water contaminated with waste motor oil with variations of airflow introduced into the water. The processes of clean water aeration and water with different oil content (mass concentration from 5 to 10 mg/L). The purpose of these investigations performed on an experimental setup were analysis of the aeration process technical indicators in correlation with the thermodynamic and kinetic parameters, related to the presence of oil in the water in order to achieve more efficient refinery wastewater purification.
Keywords: čiščenje odpadnih voda; prezračevanje; olje; prenos snovi; kisik